PENGARUH TEKANAN INJEKSI BAHAN BAKAR TERHADAP KARAKTERISTIK KABUTAN CAMPURAN SOLAR DAN DIMETIL ETER - Bambang Suwondo Rahardjo; Taufik Yuwono (Jurnal Energi dan Lingkungan (Enerlink), 2010)
Fuel spray injection plays a main role in determining the performance of dieselengines, where the spray pattern illustrates fuel combustion occurs in thecombustion chamber. Characteristics of Sauter Mean Diameter (SMD) spray isdevoted to fuel evaporation, and mixing and combustion quality affected bypressure injection (ï„P) and the physical chemical properties of the fuel (density,surface tension, viscosity and boiling point). From fuel spray test results showedthat fuel evaporation characteristics of fuel at a certain pressure effect on engineperformance. The higher the injection pressure will reduce the diameter of thefuel sprays after injection (SMD), thus speeding up evaporation and mixingprocesses between fuel and air in the combustion chamber with resulted thecombustion process is more completelyKata kunci: characteristics of fuel spray, diesel fuel, DME.